MAINSTREAMING CLIMATE JUSTICE: A CRITICAL INTEGRATION INTO INTERNATIONAL LAW AND SOCIAL EQUITY - Syeda Saima Shabbir (International Journal of Contemporary Issues in Social Sciences, 2024)
Mainstreaming climate justice as a central tenet of international law and social justice represents a critical evolution in addressing the global climate crisis. Climate justice acknowledges the disproportionate impact of climate change on marginalized and vulnerable populations, including those in developing countries, indigenous communities, and future generations. These groups, despite contributing the least to global greenhouse gas emissions, bear the brunt of climate-related impacts such as extreme weather events, rising sea levels, and loss of livelihoods. In the context of international law, mainstreaming climate justice involves embedding principles of equity and differentiated responsibility. Treaties like the Paris Agreement reflect this by recognizing that developed countries, having historically contributed more to global emissions, carry a greater obligation to reduce emissions and support developing nations in their adaptation and mitigation efforts. Furthermore, international law can serve as a framework for enforcing climate justice by establishing legal mechanisms that hold states and corporations accountable for environmental degradation and its associated human rights violations. This includes the potential expansion of international courts’ jurisdiction to hear climate-related cases and the advancement of the principle of loss and damage, which seeks compensation for those adversely affected by climate impacts. Climate justice also intersects with human rights law, advocating for the recognition of a safe and healthy environment as a fundamental human right. This approach emphasizes the need for global cooperation in addressing climate change, ensuring that efforts to combat environmental degradation are not only effective but also equitable. International cooperation, facilitated by international law, is crucial for sharing resources, technology, and knowledge to help vulnerable countries adapt to climate impacts and transition to sustainable energy systems. From a social justice perspective, climate justice is deeply intertwined with broader issues of social inequality. The impacts of climate change often exacerbate existing disparities related to race, gender, class, and geography. Mainstreaming climate justice into social justice frameworks involves advocating for policies that address these intersecting inequalities, ensuring that the burdens and benefits of climate action are distributed fairly across all segments of society. This intersectional approach recognizes that effective climate action must go beyond environmental concerns to address the underlying social and economic structures that contribute to vulnerability and inequality. By integrating climate justice into the core of international law and social justice, a more equitable and sustainable global response to the climate crisis can be achieved, ensuring that the rights and needs of the most vulnerable are prioritized in global climate governance.